ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA PT. ASKES (PERSERO) CABANG UTAMA SEMARANG - Saragih, Diana Laura Magdalena (Master of Management Diponegoro University, 2012)
The purpose of this research is to test the influences of reliability, responsiveness, assurance, empathy, and tangible on customer satisfaction. Using these variables are to solve the arising problem within PT Askes (Persero) Kantor Cabang Utama Semarang.The samples size of this research is 100 customers of PT Askes (Persero) Kantor Cabang Utama Semarang. Then data is analyzed by using multiple regression test run with the help of SPPS program. The result show that reliability, responsiveness, assurance, empathy, and tangible give positive and significant impact toward customer’s satisfaction.The empirical findings indicate that reliability give significant effect on customer satisfaction are 0,683; responsiveness give significant effect on customer satisfaction are 0,370; assurance give significant effect on customer satisfactionare 0,214; empathy give significant effect on customer satisfaction are 0,209; and tangible give significant effect on customer satisfactionare 0,234.